Solidarity economy and food production: a new configuration for agri-food chains - Martins, Ingryd Rodrigues; Reis, Adebaro Alves dos; Martins, Luiza Helena da Silva; Barbosa, Maria José de Souza; Joele, Maria Regina Sarkis Peixoto (Cooperativismo & Desarrollo, 2024)
Alternative economies are responses to conventional economic systems, such as the solidarity economy, which tend to have an impact on changes in food supply systems, aiming for a transition to sustainability. With this in mind, the article addresses the importance of the solidarity economy for food production in the interrelation between the terms solidarity economy and food. This is a comprehensive review, which its approach is organized into four sections: the first discusses the path to food security and the sustainability of food systems, demonstrating the challenges for global food security. The second refers to the principles of cooperativism, particularly its social organizations, with an emphasis on cooperatives and the solidarity economy. The third describes the influence of short chains on alternative food supply networks, based on an overview of the interdisciplinary dimension of these short food circuits. And finally, the fourth covers the debate on organic production as an alternative in food networks, presenting innovations achieved by organic farming. This is an analysis of studies already carried out on the global food system linked to a complex multifactorial dimension, in which organic farming and the solidarity economy can be an alternative to the transition to sustainability in food production chains.